Immobilization of the photoactive protein bacteriorhodopsin on zinc oxide Application in Bio-Sensitized Solar Cells - Martínez-Brenes, Alejandro (2019)
This project deals with the development of photoanodes for sensitized solar cells using the photoactive protein bacteriorhodopsin (BR) as the sensitizer. The purpose was to integrate the protein in substitution of the commonly used Ru-base dyes, which are expensive and toxic. Substrates were prepared by spreading a thin film of zinc oxide (ZnO) nanoparticles (NPs) over conductive transparent glass. The photoanode capable of convert the energy of light directly into electricity was completed by immobilizing the protein in the substrate. The techiniques dropcasting (DC), pheniltriethoxysilane chemical functionalization (PTES) and electrophoretic sedimentation (SE) were optimized to immobilized the protein. Through ultraviolet spectroscopy absorbance (UV-VIS) analysis was assessed the remaining photoactive functionality of the protein after immobilization. The charge transfer resistance of the photoanodes in the electrolyte were compared by electrochemical impedance curves, for all the methods it was found relatively high values (105 Ω) in comparison with the Ru-base dyes. The performance of the photoanodes prepared as sensitized solar cells with DC and SE techniques, were determined by chronopotentiometry and electrochemical impedance under illumination. It was found that the molecular layer of PTES allows to reduce the time to impregnated the BR but induced an additional electrical resistance and thus is not appropriate for the studied photoelectrochemical system. The photoanodes prepared by SE archived the highest photovoltage (16 mV), while with the DC, photovoltage of merely 1mV were obtained. These results suggest that the orientation of the protein in the ZnO was determinant in the cell photoresponse because under the electric field applied with the SE, the protein is forced to be oriented according to its electric dipole while with DC technique, the orientation is random and uncontrollable. On the basis of the results obtained, it is recommended to have a better control of the protein film thickness, use an electrolyte more compatible to the protein naturalness and reduce the ZnO thin film roughness in order to produce more efficient photoanodes.